Pengaruh Kualitas Layanan BRIMO, Bauran Promosi dan Tingkat Persaingan Terhadap Kepuasan Nasabah : Survey Pada Nasabah Pengguna BRIMO BRI Kantor Cabang Tasikmalaya - Alfanur Rosid, Andris; Mulyana, Deden; Komaludin, Ade (JOURNAL INTELEKTUAL, 2023)
Introduction/Main Objectives: To determine and analyze: the quality of BRIMO services, the promotion mix and the level of competition on customer satisfaction at BRI Tasikmalaya Branch Office either partially or simultanously. Background Problems: Banking competition in Indonesia is currently increasing, therefore BRI Kanca Tasikmalaya must be able to increase customer satisfaction by paying attention to the quality of BRIMO services, promotion mix and level of competition. Novelty: There is no research on the level of competition on satisfaction. Research Methods: This study uses path analysis with the help of the SPSS V.20 program. Finding/Results: BRIMO's service quality, promotion mix and level of competition had a positive and significant effect on customer satisfaction both partially and simultanously. Conclusion: BRIMO's service quality is in the very good category, the promotion mix is in the very good category, the level of competition is in the good category and customer satisfaction is in the very good category.